CNS Embryonal Tumor with PLAGL Amplification, a New Tumor in Children and Adolescents: Insights from a Comprehensive MRI Analysis - Tietze, A; Bison, B; Engelhardt, J; Fenouil, T; Figarella-Branger, D; Goebell, E; Hakumäki, J; Koscielniak, E; Ludlow, L E; Meyronet, D; Nyman, P; Øra, I; et al. (AJNR. American journal of neuroradiology, 2025)
BACKGROUND AND PURPOSE: CNS embryonal tumor with pleomorphic adenoma gene-like 1 (PLAGL1)/pleomorphic adenoma gene-like 2 (PLAGL2) amplification (ET, PLAGL) is a newly identified, highly malignant pediatric tumor. Systematic MRI descriptions of ET, PLAGL are currently lacking. MATERIALS AND METHODS: MRI data from 19 treatment-naïve patients with confirmed ET, PLAGL were analyzed. Evaluation focused on anatomic involvement, tumor localization, MRI signal characteristics, DWI behavior, and the presence of necrosis and hemorrhage. Descriptive statistics (median, interquartile range, percentage) were assessed. RESULTS: Ten patients had PLAGL1 and nine had PLAGL2 amplifications. The solid components of the tumors were often multinodular with heterogeneous enhancement (mild to intermediate in 47% and intermediate to strong in 47% of cases). Nonsolid components included cysts in 47% and necrosis in 84% of the cases. The tumors showed heterogeneous T2WI hyper- and isointensity (74%), relatively little diffusion restriction (ADC values less than contralateral normal-appearing WM in 36% of cases with available DWI), and tendencies toward hemorrhage/calcification (42%). No reliable distinction was found between PLAGL1- and PLAGL2-amplified tumors or compared with other embryonal CNS tumors. CONCLUSIONS: The study contributes to understanding the imaging characteristics of ET, PLAGL. It underscores the need for collaboration in studying rare pediatric tumors and advocates the use of harmonized imaging protocols for better characterization.
Keywords: Magnetic Resonance Imaging; Neoplasms, Germ Cell and Embryonal; nádory mozku; Sensitivity and Specificity; magnetická rezonanční tomografie; senzitivita a specificita; DNA-Binding Proteins; Humans; Infant; kojenec; DNA vazebné proteiny; Brain Neoplasms; dítě; Transcription Factors; Child; Female; amplifikace genu; lidé; gen SMARCB1; germinální a embryonální nádory; reprodukovatelnost výsledků; předškolní dítě; SMARCB1 Protein; ženské pohlaví; Gene Amplification; Male; Reproducibility of Results; Adolescent; transkripční faktory; mužské pohlaví; Child, Preschool; mladiství